Weak-field ELF magnetic interactions: Implications for biological change during paleomagnetic reversals. (December 2013) - Liboff, Abraham R.
<x xml:space="preserve">Abstract</x> Contrary to the belief that paleomagnetic reversals are not biologically significant, we find good reason to think otherwise. Attention is drawn to polarity transitions, time intervals a few thousand years long that follow the collapse of the existing geomagnetic dipole moment and precede the establishment of the new, oppositely directed moment. The geomagnetic field during transitions is reduced to a maximal mean intensity about 10% of the stable field and can exhibit low-frequency perturbations comparable to numerous laboratory-based extremely low frequency (ELF) studies reporting biological interactions, making it very likely that similar interactions must occur over the course of a polarity transition. This conclusion is strengthened by reports of medical problems that significantly correlate with intense solar winds, events that also generate ELF perturbations similar to those that can occur during polarity transitions.